2022
DOI: 10.55563/clinexprheumatol/0ddt88
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram to predict dermatomyositis prognosis: a population-based study of 457 cases

Abstract: ObjectiveDermatomyositis (DM) is a systemic autoimmune disease, which typically affects the striated muscle with a variable involvement of the skin and other organs. Clinically amyopathic DM (CADM) is a combination of hypomyopathic DM (HDM) and amyopathic DM (ADM), with a characteristic of skin-predominant lesions. To date, large-scale studies on the prognostic factors of DM/CADM have been limited. The aim of this study is to evaluate the prognostic values of clinical manifestations in DM/CADM and to develop a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Compared with merely identifying risk factors, establishment of a predictive model would not only assist in deepening our comprehensive understanding of IIMs and its complications, but also provide an efficient and instant tool for clinical practice. In preceding studies concerning adult or juvenile IIMs, various predictive models for prognosis, positivity of anti-MDA5 antibody, complication of hypertension, RP-ILD, sHLH and malignancy [ 19 , 42 45 ] have been constructed. To date, this is the first study seeking to construct a comprehensive clinical model for prediction and early identification of MI in IIMs patients.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with merely identifying risk factors, establishment of a predictive model would not only assist in deepening our comprehensive understanding of IIMs and its complications, but also provide an efficient and instant tool for clinical practice. In preceding studies concerning adult or juvenile IIMs, various predictive models for prognosis, positivity of anti-MDA5 antibody, complication of hypertension, RP-ILD, sHLH and malignancy [ 19 , 42 45 ] have been constructed. To date, this is the first study seeking to construct a comprehensive clinical model for prediction and early identification of MI in IIMs patients.…”
Section: Discussionmentioning
confidence: 99%
“…4-5), which is rarely reported. Some studies reported that ANA was related to the prognosis of immune diseases, such as systemic lupus erythematosus 33 , dermatomyositis 34 . Notably, whether or not ANA could predict the prognosis outcome of AIH remains to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…4 , 5 ), which is rarely reported. Furthermore, some studies also reported that ANA was related to the prognosis of immune diseases [ 35 , 36 ], such as systemic lupus erythematosus, dermatomyositis. However, whether or not ANA could predict the prognosis outcome of AIH remains to be further studied.…”
Section: Discussionmentioning
confidence: 99%